An M1AP homozygous splice‐site mutation associated with severe oligozoospermia in a consanguineous family. Issue 5 (10th February 2020) - Tu, Chaofeng; Wang, Ying; Nie, Hongchuan; Meng, Lanlan; Wang, Weili; Li, Yong; Li, Dongyan; Zhang, Huan; Lu, Guangxiu; Lin, Ge; Tan, Yue‐Qiu; Du, Juan
Abstract: Severe oligozoospermia (SO) is an important cause of male infertility. Its etiology and pathogenesis are associated with genetic abnormalities; however, the genetic causes of the majority of idiopathic human SO remain unclear. Here, we report a homozygous splice‐site mutation in M1AP (meiosis 1 associated protein; NM_138804, c.1435‐1G>A) observed in a patient with SO from a consanguineous Han Chinese family. His parents and fertile brother were heterozygous for the mutation. The splice variant led to a lack of M1AP protein in the patient's spermatozoa. Ultrastructural and immunostaining analyses of patient's spermatozoa showed highly aberrant swollen mitochondrial sheaths with normal axonemal structures. Subsequent mutation screening identified three additional heterozygous M1AP variants in 4/243 subjects with idiopathic SO, but no M1AP variants among 223 fertile subjects. Additionally, a previously study reported that M1ap knock‐out mice exhibited SO due to meiotic arrest. Hence, our findings indicate that M1AP mutation might represent novel genetic alteration responsible for human SO. Abstract : (A) Pedigree and Sanger sequencing analysis of the family. (B) The effect of the splice‐split variant in the M1AP gene. (C) Aberrant swollen mitochondrial sheath in sperm flagella of M1AP mutant spermatozoa.